The First Sense : A Philosophical Study of Human Touch - Fulkerson, Matthew, 1977- (Book collections on Project MUSE., 2014)
Fulkerson offers a philosophical account of human touch, one informed and constrained by empirical work on touch. He begins by arguing that human touch, despite its functional diversity, is a single, unified sensory modality. From there, he describes and argues for a novel, unifying role for exploratory action in touch. Later chapters fill in the details of this unified, exploratory form of perception, offering philosophical accounts of tool use and distal touch, the representational structure of tangible properties, the spatial content of touch, and the role of pleasure in tactual experience.